Quantificação de metilmercúrio em sedimento e organismos fitoplanctônicos : estudo do caso da área contaminada de Descoberto - Minas Gerais - Louise Aparecida Mendes (2017)
In 2002, metallic Hg was found buried in a rural area of Descoberto city, Brazil, and although a number of studies have been conducted in order to assess the contamination of the area, none of them investigated the presence of methylated Hg in the hydric system. In this work methylmercury (CH3Hg+) was determined using gaschromatography-pyrolysis-atomic fluorescence detection (CG-pyro-AFS) in material from rain sedimentation boxes and stream sediments near the contaminated area. Total Hg (HgT) concentration along with the chemical speciation by thermo-desorption were performed. The HgT concentration in material from the sedimentation boxes was foundto be very high, up to 41,580 g kg-1. The samples from the Grama and Rico streams show a range of HgT from 5.8 to 266 g kg-1. The thermo-desorption analysis showed predominance of Hg2+, with a good positive correlation with organic matter and total sulfur. The CH3Hg+ concentration in stream sediment samples ranged from <0.04 to1.87 g kg-1and in the samples of sedimentation boxes the concentrations were 1.33 and 8.0 g kg-1 during dry season. These are high values show that care should be taken to avoid the transport of this material to the hydrological system. Chapters 2 and 4 describe the validation of two methods for determination of CH3Hg+ by GC-pyro-AFS: sediment samples and cyanobacteria. Sediment is one of themajor sites of CH3Hg+ production and cyanobacteria are likely responsible for the biotransformation of mercury (Hg) into this species. The whole validation procedure followed the protocols of INMETRO guide DOQ-CGCRE-008. The results showed that the two methods do not present matrix effect; good linearity (0.994) in the range of 0 to 400 pg CH3Hg+; repeatability of 3%; intermediate precision of 8%. Spiked recovery assays of samples in the range of 93 to 129%; and detection limits of 0.04 g kg-1 of sediment and 1.3 g kg-1 of cyanobacteria. Reference materials CRM580 and DORM-3 were used to evaluate the accuracy of the method, resulting in 95 and 89% recoveries,respectively. The methods were, therefore, adequate for the proposed objective and can be used as important tools in routine analyzes and/or studies of the biogeochemical cycle of Hg. The methylation assay of Hg2+ showed that the microalgae Stichococcus sp. collected in the contaminated area of Descoberto may be responsible for theproduction of CH3Hg+.